OP29 Ethnic and Socioeconomic Influences on Childhood Blood Pressure: The Child Heart and Health Study in England (Chase). (17th September 2012) - Thomas, C; Nightingale, CM; Donin, A; Rudnicka, AR; Owen, CG; Cook, D; Whincup, PH
Abstract : Background: Compared to UK white European adults, UK black African-Caribbean adults have higher mean systolic (SBP) and diastolic (DBP) blood pressure; UK South Asian adults have higher mean DBP but lower SBP. However, information on blood pressure in UK children from different ethnic groups is limited. The aim of this study was to compare blood pressure levels in UK children of black African-Caribbean, South Asian and white European origin. Methods: A cross sectional study of 5, 666 UK primary school children of South Asian, black African Caribbean, and white European origin aged 9 to 10 years was undertaken. Ethnic and socioeconomic differences in SDP and DBP (as means and differences with their 95% confidence intervals) were obtained from multilevel linear regression models fitting school as a random effect in order to take account of the natural clustering of children within school. All analyses were adjusted for sex, age, month of assessment, blood pressure observer, room temperature and time of day of measurement fitted as fixed effects. The effects of adjustment for height, adiposity (fat mass index, sum of skinfolds) fitted as continuous variables, and socioeconomic circumstances on ethnic differences in blood pressure were then explored. Results: After adjustment for height and adiposity, black African-Caribbean children had a lower mean SBP than white Europeans (mean difference 1.62 mmHg, 95% CI 0.86, 2.38 mmHg), while mean DBP was similar (mean difference 0.58 mmHg, 95%CI –0.12, 1.28 mmHg). The mean SBP difference was particularly marked in black African children. In similar analyses, South Asian children had a lower mean SBP (mean difference 1.10 mmHg, 95%CI 0.34, 1.86 mmHg) than white Europeans and a higher mean DBP (mean difference 1.07 mmHg, 95%CI 0.37, 1.76 mmHg). The mean DBP difference was particularly marked among Indian and Bangladeshi, rather than Pakistani, children. Blood pressure was largely unrelated to socioeconomic circumstances; the ethnic differences in blood pressure were not affected by socioeconomic adjustment. Conclusion: A blood pressure pattern similar to that in adults is present in UK South Asian but not in UK black African-Caribbean children at 9–10 years. This suggests that key determinants of ethnic differences in blood pressure operate at different stages of the life course in these different ethnic groups. Understanding the reasons for the early emergence of ethnic differences in blood pressure (particularly among South Asians) is an important research priority.